A Comparison of Wound Complications and Post-operative Factors Following the Use of Hydrodissection for Mastectomy in Breast Cancer Patients - Ismail, Muhammad Aizat Tamlikha; Abdullah Suhaimi, Shahrun Niza; Abdul Latiff, Juliana; Baharudin, Suraya; Azhar Shah, Shamsul (IIUM Medical Journal Malaysia, 2022)
Introduction: Mastectomy with axillary clearance remains the hallmark of breast cancer treatment. The conventional use of electrocautery has been associated with the risk of post-operative complications. Hydrodissection may reduce surgery time and produce fewer wound complications with less post-operative pain. The aim of this study was to compare these 2 modalities. Materials & Methods: This prospective randomised control trial was performed with breast cancer patients in Hospital Selayang, Malaysia, between 1 June 2019 to 1 September 2020. The patients were randomised into conventional and hydrodissection groups. The outcomes of interest were post-operative wound complications and other post-operative factors. A chi-square test and independent Student t-test were used to compare the 2 groups. Result: A total of 94 patients were recruited. There was a significant reduction in post-operative seroma in the hydrodissection group compared to the conventional group (40.4 vs 19.1, p<0.05). The surgery in the hydrodissection group was also shorter (114.09 vs 100.15, p<0.05), and there was less 24-hour post-operative pain (3.28 vs 2.13, p<0.05). However, no significant association was observed with other post-operative wound complications (i.e. flap necrosis, surgical site infection and hematoma) or other post-operative factors (i.e. estimated blood loss, mean volume of drain and duration of drain). It was also demonstrated that the hydrodissection technique lowers the risk of developing seroma 3-fold (odds ratio=0.349, p<0.05). Conclusion: The use of hydrodissection with liposuction cannula reduced the rate of post-operative seroma and provided a shorter operative duration and better post-operative pain control.